Peran Guru dalam Menanamkan Pendidikan Karakter Peserta Didik Menurut Pandangan Islam - Nafiudin Nafiudin; Muhammad Fazlur Rahman Hadi; Mahsun Jayadi (Dinasti Review, 2024)
The indicator of the progress of an institution is not only seen from the number of students, but also the quality of the ability of students and graduates, not only in academic achievement but also in non-academic fields, performance, including student attitudes and behavior. The author sometimes finds that although the school is classified as Islamic, it is less able to foster the religious dimension of students. If there is a deviation of religious norms, the first perpetrator is the teacher. In fact, building the religious dimension and strengthening student character is our common task as school community. Education is the key to developing children's personality from an early age, because the essence of education is not only providing knowledge but also providing values. All of this will help shape the personality of the nation's children with noble character and overcome juvenile delinquency due to various social deviations. When a person's character is primarily based on religious values, a strong spirit of character is born, which is also the core of a strong nation. The main purpose of character education in Islam is to develop the character of students to have good moral and cultural sensitivity and be able to implement it in everyday life. The main purpose of character education in Islam is to develop the character of students to have good moral and cultural sensitivity and be able to implement it in everyday life. The purpose of this article is none other than so that everyone knows that teachers have an important role in shaping the next generation of the nation with good character. So as not to deviate from Islamic teachings and not commit immoral acts. This research was conducted by means of qualitative research by conducting interviews, observations and documentation to obtain valid data or information needed by the author.